2020
DOI: 10.3389/fdmed.2020.575010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Endodontic Access Cavity Design on Fracture Strength of Maxillary Incisors and Premolars and on Fatigue Resistance of Reciprocating Instruments

Abstract: The aim of this study was to compare the effect of two different access cavity designs on fracture strength of endodontically treated teeth and on cyclic fatigue resistance of Reciproc blue instruments. Methods: Forty (40) maxillary central incisor teeth and forty (40) upper first premolars were selected and divided into 4 groups (n = 20/group): Group 1A, incisors prepared with conservative access cavity (CEC); group 1B, incisors prepared with traditional access cavity (TEC); group 2A, premolars prepared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…One of the most important methodological aspects of research design is the creation of a reliable baseline inasmuch as anatomical discrepancies of sampling may have a direct impact on the outcome. Although it seems logical that a proper anatomical pairing of teeth allocated for each experimental group may compromise the final conclusions, several studies performed sample selection based only on two‐dimensional radiographs (Corsentino et al, 2018; Krishan et al, 2014; Moore et al, 2016), external measurement of teeth (Corsentino et al, 2018; Ivanoff et al, 2017; Marinescu et al, 2020; Maske et al, 2021; Özyürek et al, 2017; Plotino et al, 2017; Roperto et al, 2019; Saberi et al, 2020; Sabeti et al, 2018; Spicciarelli et al, 2020) or merely by random allocation into the experimental groups (Chlup et al, 2017; Makati et al, 2018; Mustafa et al, 2020; Reddy et al, 2020). To overcome these sampling limitations, De‐Deus et al (2020) demonstrated that micro‐CT technology is the recommended method to pair‐match extracted teeth based on their anatomical characteristics (Figure 24).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the most important methodological aspects of research design is the creation of a reliable baseline inasmuch as anatomical discrepancies of sampling may have a direct impact on the outcome. Although it seems logical that a proper anatomical pairing of teeth allocated for each experimental group may compromise the final conclusions, several studies performed sample selection based only on two‐dimensional radiographs (Corsentino et al, 2018; Krishan et al, 2014; Moore et al, 2016), external measurement of teeth (Corsentino et al, 2018; Ivanoff et al, 2017; Marinescu et al, 2020; Maske et al, 2021; Özyürek et al, 2017; Plotino et al, 2017; Roperto et al, 2019; Saberi et al, 2020; Sabeti et al, 2018; Spicciarelli et al, 2020) or merely by random allocation into the experimental groups (Chlup et al, 2017; Makati et al, 2018; Mustafa et al, 2020; Reddy et al, 2020). To overcome these sampling limitations, De‐Deus et al (2020) demonstrated that micro‐CT technology is the recommended method to pair‐match extracted teeth based on their anatomical characteristics (Figure 24).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Two studies using mandibular molars (Silva et al, 2021a), maxillary central incisors, and maxillary first premolars (Spicciarelli et al, 2020) compared the influence of ConsAC (Spicciarelli et al, 2020) and UltraAC (Silva et al, 2021a) to TradAC regarding the cyclic fatigue resistance of reciprocating instruments. In both studies, instruments used in teeth prepared with minimally invasive access cavities were associated with less cyclic fatigue resistance values than in teeth with TradAC.…”
Section: Influence Of Minimally Invasive Access Cavity On Endodontic ...mentioning
confidence: 99%
See 3 more Smart Citations